Guidelines for perioperative care in gynecologic/oncology: Enhanced Recovery After Surgery (ERAS) Society recommendations—2019 update. Issue 4 (15th March 2019) - Nelson, Gregg; Bakkum-Gamez, Jamie; Kalogera, Eleftheria; Glaser, Gretchen; Altman, Alon; Meyer, Larissa A; Taylor, Jolyn S; Iniesta, Maria; Lasala, Javier; Mena, Gabriel; Scott, Michael; Gillis, Chelsia; et al.
Abstract : Background: This is the first updated Enhanced Recovery After Surgery (ERAS) Society guideline presenting a consensus for optimal perioperative care in gynecologic/oncology surgery. Methods: A database search of publications using Embase and PubMed was performed. Studies on each item within the ERAS gynecologic/oncology protocol were selected with emphasis on meta-analyses, randomized controlled trials, and large prospective cohort studies. These studies were then reviewed and graded according to the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system. Results: All recommendations on ERAS protocol items are based on best available evidence. The level of evidence for each item is presented accordingly. Conclusions: The updated evidence base and recommendation for items within the ERAS gynecologic/oncology perioperative care pathway are presented by the ERAS® Society in this consensus review.